2017
DOI: 10.4172/2161-0711.1000566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stress on Academic Performance of Undergraduate Medical Students

Abstract: Medical students experience stress during their academic years. This stress is related to financial issues, health problems, social issues and academic difficulties. Stress can either negatively or positively influence academic achievements. The aim of this study is to explore the relationship between stress and academic performance of medical students and identify sources of stress effecting academic performances.All the medical students of undergraduate third year at Sheikh Zayed Medical College, Rahim Yar K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
5
1
1
Order By: Relevance
“…They compared the academic performance in relation to level of stress among undergraduate medical students, and concluded that little stress is necessary to accomplish the task and can improve performance. 17 Another study showed similar results that Female students show greater anxiety and increased emotional responses to complete the assigned tasks as compared to male students. 18 Regarding the responses that were collected by distributing the questionnaire, only 50% students agreed that the tasks given were easy to understand and problem based scenarios were considered difficult by 50% respondents.…”
Section: Discussionmentioning
confidence: 76%
“…They compared the academic performance in relation to level of stress among undergraduate medical students, and concluded that little stress is necessary to accomplish the task and can improve performance. 17 Another study showed similar results that Female students show greater anxiety and increased emotional responses to complete the assigned tasks as compared to male students. 18 Regarding the responses that were collected by distributing the questionnaire, only 50% students agreed that the tasks given were easy to understand and problem based scenarios were considered difficult by 50% respondents.…”
Section: Discussionmentioning
confidence: 76%
“…On their turn, students with low resilience may be deprived by the buffer effect of resilience on the relationship between adjustment problems and academic performance [81]. Lastly, perceived stress has been consistently reported as a distinct variable able to negatively influence academic achievement, via multiple, sometimes complimentary mechanisms [82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…Studiju literatūras pieejamība ir īpaši aktuāla nepilna laika studējošajiem un tiem jauniešiem, kas strādā paralēli studiju procesam. Grūtības atrast nepieciešamo studiju literatūru būtiski apgrūtina noteikta studiju kursa apguvi un paaugstina studējošo stresa līmeni (Haider, 2017;Walsh et al, 2010).…”
Section: Socio-psychological Aspects Of Study Stressorsunclassified